Making Meaning: A Critical Literature Review of Young Adults’ Post-Katrina Volunteer Experiences - Jessie Baginski; Elice Rogers; Catherine Hansman (Adult Education Research Conference, 2010)
Hurricane Katrina dealt a devastating blow to the soul of America which resulted in a collective response of young adult volunteers. Understanding the experiences of these crisis volunteers can provide meaningful insight and underscore the importance of investigating human resilience, civic operations, and self-perceptions for life-long learning curricula.